Cytosine arabinofuranoside-induced activation of astrocytes increases the susceptibility of neurons to glutamate due to the release of soluble factors - Ahlemeyer, Barbara; Kölker, Stefan; Zhu, Yuan; Hoffmann, Georg F.; Krieglstein, Josef (Neurochemistry international, 2003)
Activation of astrocytes occurs during many forms of CNS injury, but its importance for neuronal survival is poorly understood. When hippocampal cultures of neurons and astrocytes were treated from day 2-4 in vitro (DIV 2-4) with 1μM cytosine arabinofuranoside (AraC), we observed a stellation of astrocytes, an increase in glial fibrillary acidic protein (GFAP) level as well as a higher susceptibility of the neurons to glutamate compared with cultures treated from DIV 2-4 with vehicle. To find out whether factors released into the culture medium were responsible for the observed differences in glutamate neurotoxicity, conditioned medium of AraC-treated cultures (MCMAraC) was added to vehicle-treated cultures and conditioned medium of vehicle-treated cultures (MCMvh) was added to AraC-treated cultures 2h before and up to 18h after the exposure to 1mM glutamate for 1h. MCMAraC increased glutamate neurotoxicity in vehicle-treated cultures and MCMvh reduced glutamate neurotoxicity in AraC-treated cultures. Heat-inactivation of MCMvh increased, whereas heat-inactivation of MCMAraC did not affect glutamate toxicity suggesting that heat-inactivation changed the proportion of factors in MCMvh inhibiting and exacerbating the excitotoxic injury. Similar findings were obtained using conditioned medium of pure astrocyte cultures of DIV 12 treated from DIV 2-4 with vehicle or 1μM AraC suggesting that heat-sensitive factors in MCMvh were mainly derived from astrocytes. Treatment of hippocampal cultures with 1mM dibutyryl-cAMP for 3 days induced an activation of the astrocytes similar to AraC and increased neuronal susceptibility to glutamate. Our findings provide evidence that activation of astrocytes impairs their ability to protect neurons after excitotoxic injury due to changes in the release of soluble and heat-sensitive factors.
Gesehen am 22.12.2020